Evidence for increases in vegetation species richness across UK Environmental Change Network sites linked to changes in air pollution and weather patterns. (September 2016) - Rose, Rob; Monteith, Don T.; Henrys, Peter; Smart, Simon; Wood, Claire; Morecroft, Mike; Andrews, Chris; Beaumont, Deborah; Benham, Sue; Bowmaker, Victoria; Corbett, Stuart; Dick, Jan; et al.
Abstract: We analysed trends in vegetation monitored at regular intervals over the past two decades (1993–2012) at the twelve terrestrial Environmental Change Network (ECN) sites. We sought to determine the extent to which flora had changed and link any such changes to potential environmental drivers. We observed significant increases in species richness, both at a whole network level, and when data were analysed within Broad Habitat groupings representing the open uplands, open lowlands and woodlands. We also found comparable increases in an indicator of vegetation response to soil pH, Ellenberg R. Species characteristic of less acid soils tended to show more consistent increases in frequency across sites relative to species with a known tolerance for strongly acidic soils. These changes are, therefore, broadly consistent with a response to increases in soil solution pH observed for the majority of ECN sites that, in turn, are likely to be driven by large reductions in acid deposition in recent decades. Increases in species richness in certain habitat groupings could also be linked to increased soil moisture availability in drier lowland sites that are likely to have been influenced by a trend towards wetter summers in recent years, and possibly also to a reduction in soil nitrogen availability in some upland locations. Changes in site management are also likely to have influenced trends at certain sites, particularly with respect to agricultural practices. Our results are therefore indicative of widescale responses to major regional-scale changes in air pollution and recent weather patterns, modified by local management effects. The relative consistency of management of ECN sites over time is atypical of much of the wider countryside and it is therefore not appropriate to scale up these observations to infer national scale trends. Nevertheless the results provide an important insight into processes that may be operating nationally. It will now be necessary to test for the ubiquity of these changes using appropriate broader spatial scale survey data.